Battery pole piece, battery diaphragm, electrochemical battery and preparation method
By introducing fast ion material into the battery electrode sheet and separator of electrochemical energy storage batteries to form a three-dimensional network structure, the problem of local action of fast ion transport materials in the prior art is solved, and the rate performance of electrochemical batteries is significantly improved.
Patent Information
- Application Number
- CN202311015242.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-11
- Publication Date
- 2025-02-18
AI Technical Summary
When the prior art uses fast ion transport materials in electrochemical energy storage batteries, the ion conduction performance can only be locally improved, resulting in limited improvement of battery rate performance.
By introducing fast ion material into the battery electrode sheet and the battery separator, a three-dimensional network structure is formed to be distributed on the gaps and surfaces of the electrode material layer and the separator body, thereby building a three-dimensional ion conductor dielectric network to improve the migration rate of active ions.
The rapid charging and discharge capacity of electrochemical batteries under large-scale operating conditions is achieved, which significantly improves the rate performance of electrochemical batteries, especially in high-current operating conditions, and obtains stronger rate performance.
Smart Images

Figure CN119481052A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the technical field of electrochemical cells, and in particular to a battery pole piece, a battery separator, an electrochemical cell and a preparation method thereof. Background Art
[0002] Electrochemical energy storage batteries include lithium-ion batteries, sodium-ion batteries, potassium-ion batteries, etc. Electrochemical energy storage batteries usually include a positive electrode, a negative electrode, a battery separator and an electrolyte. The positive electrode includes a positive electrode current collector and a positive electrode material layer located thereon, and the negative electrode includes a negative electrode current collector and a negative electrode material layer located thereon. When used, active ions such as lithium ions, sodium ions, and potassium ions circulate between the positive and negative electrodes to achieve energy storage.
[0003] Fast ion transport materials have the characteristics of fast ion transport speed, strong ion transport capacity, and low resistivity. They are also called fast ion conductors. They are usually used in electrochemical energy storage batteries to improve their rate performance. For example, some common technical measures are to set a fast ion transport material layer on the surface of the positive or negative active material, physically add fast ion additives to the battery slurry, and coat a fast ion material layer on the surface of the battery electrode and / or battery separator.
[0004] However, the related art regarding the arrangement of fast ion transport materials in electrochemical energy storage batteries can only improve the ion conduction performance in a local area of the electrochemical energy storage battery, resulting in limited effect on improving the battery rate performance.
[0005] Public Content
[0006] In view of this, the present disclosure provides a battery pole piece, a battery separator, an electrochemical cell and a preparation method, which can solve the technical problems in the related art.
[0007] Specifically, the following technical solutions are included:
[0008] In one aspect, a battery pole piece is provided, the battery pole piece comprising a current collector and an electrode material layer located on a surface of the current collector;
[0009] The electrode material layer includes: an active material, a conductive agent, a binder and a fast ion material. The active material, the conductive agent and the fast ion material are combined with the binder and integrally bonded to the current collector. The fast ion material is distributed in the electrode material layer in a three-dimensional network structure, and the fast ion material is located in the internal gaps and surface of the electrode material layer.
[0010] The battery pole piece provided by the embodiment of the present disclosure forms an electrode material layer by combining active materials, conductive agents and binders, and distributes fast ion materials in the electrode material layer in a three-dimensional network structure, and the fast ion materials in the three-dimensional network structure are located in the gaps and surface of the electrode material layer. In this way, the fast ion materials form a three-dimensional ion conductor medium network in the battery pole piece, and the three-dimensional ion conductor medium network has good uniformity and penetration characteristics, so that it can act on the entire area of the battery pole piece, and can improve the migration rate of active ions in the entire area of the battery pole piece, thereby releasing more of the fast charging and discharging capacity of the electrochemical cell under high-rate conditions, effectively improving the rate performance of the electrochemical cell, and especially can promote the electrochemical cell to obtain stronger rate performance under high-current conditions.
[0011] In some possible implementations, the fast ion material is attached to a surface of at least one of the active material, the conductive agent, and the binder.
[0012] In some possible implementations, the battery pole piece is used for a lithium-ion battery, and the fast ion material is at least one of a lithiated phosphorus-sulfur compound, a lithiated silicon-sulfur compound, a lithiated germanium-sulfur compound, a lithiated tin-sulfur compound, a lithiated silicon-phosphorus compound, a lithiated germanium-phosphorus compound, a lithiated tin-phosphorus compound, a lithiated silicon-phosphorus-sulfur compound, a lithiated germanium-phosphorus-sulfur compound, and a lithiated tin-phosphorus-sulfur compound;
[0013] Alternatively, the battery pole piece is used for a sodium ion battery, and the fast ion material is at least one of a sodium-containing phosphorus-sulfur compound, a sodium-containing silicon-sulfur compound, a sodium-containing germanium-sulfur compound, a sodium-containing tin-sulfur compound, a sodium-containing silicon-phosphorus compound, a sodium-containing germanium-phosphorus compound, a sodium-containing tin-phosphorus compound, a sodium-containing silicon-phosphorus-sulfur compound, a sodium-containing germanium-phosphorus-sulfur compound, and a sodium-containing tin-phosphorus-sulfur compound;
[0014] Alternatively, the battery pole piece is used for a potassium ion battery, and the fast ion material is at least one of a potassium-containing phosphorus-sulfur compound, a potassium-containing silicon-sulfur compound, a potassium-containing germanium-sulfur compound, a potassium-containing tin-sulfur compound, a potassium-containing silicon-phosphorus compound, a potassium-containing germanium-phosphorus compound, a potassium-containing tin-phosphorus compound, a potassium-containing silicon-phosphorus-sulfur compound, a potassium-containing germanium-phosphorus-sulfur compound, and a potassium-containing tin-phosphorus-sulfur compound.
[0015] In some possible implementations, the mass of the fast ion material is 0.1%-20% of the total mass of the electrode material layer. The mass of the fast ion material is within the above range to ensure that it can be evenly distributed in the gaps and surfaces of the entire area of the electrode material layer.
[0016] On the other hand, a battery separator is provided, comprising a separator body and a fast ion material, wherein the fast ion material is distributed in the separator body in a three-dimensional network structure, and the fast ion material is at least located in the gaps and surface of the separator body.
[0017] The battery diaphragm provided by the embodiment of the present disclosure makes the fast ion material distributed in the gaps and surface of the diaphragm body in a three-dimensional network structure. In this way, the fast ion material forms a three-dimensional ion conductor medium network in the diaphragm body. The three-dimensional ion conductor medium network has good uniformity and penetration characteristics, so that it can act on the entire area of the diaphragm body, and can improve the migration rate of active ions in the entire area of the diaphragm body, thereby facilitating the rapid release of the charge and discharge capacity of the electrochemical battery under high-rate conditions, effectively improving the rate performance of the electrochemical battery, and especially promoting the electrochemical battery to obtain stronger rate performance under high-current conditions.
[0018] In some possible implementations, the battery separator is used for a lithium-ion battery, and the fast ion material is at least one of a lithiated phosphorus-sulfur compound, a lithiated silicon-sulfur compound, a lithiated germanium-sulfur compound, a lithiated tin-sulfur compound, a lithiated silicon-phosphorus compound, a lithiated germanium-phosphorus compound, a lithiated tin-phosphorus compound, a lithiated silicon-phosphorus-sulfur compound, a lithiated germanium-phosphorus-sulfur compound, and a lithiated tin-phosphorus-sulfur compound;
[0019] Alternatively, the battery separator is used for a sodium ion battery, and the fast ion material is at least one of a sodium-containing phosphorus-sulfur compound, a sodium-containing silicon-sulfur compound, a sodium-containing germanium-sulfur compound, a sodium-containing tin-sulfur compound, a sodium-containing silicon-phosphorus compound, a sodium-containing germanium-phosphorus compound, a sodium-containing tin-phosphorus compound, a sodium-containing silicon-phosphorus-sulfur compound, a sodium-containing germanium-phosphorus-sulfur compound, and a sodium-containing tin-phosphorus-sulfur compound;
[0020] Alternatively, the battery separator is used for a potassium ion battery, and the fast ion material is at least one of a potassium-containing phosphorus-sulfur compound, a potassium-containing silicon-sulfur compound, a potassium-containing germanium-sulfur compound, a potassium-containing tin-sulfur compound, a potassium-containing silicon-phosphorus compound, a potassium-containing germanium-phosphorus compound, a potassium-containing tin-phosphorus compound, a potassium-containing silicon-phosphorus-sulfur compound, a potassium-containing germanium-phosphorus-sulfur compound, and a potassium-containing tin-phosphorus-sulfur compound.
[0021] In some possible implementations, the mass of the fast ion material is 0.1%-20% of the total mass of the battery separator. The mass of the fast ion material is within the above range to ensure that it can be evenly distributed in the gaps and surfaces of the entire area of the separator body.
[0022] In yet another aspect, an electrochemical cell is provided, comprising at least one of any of the battery electrodes described above and any of the battery separators described above.
[0023] The electrochemical cell provided in the embodiments of the present disclosure is also a secondary battery, which has all the advantages of the battery pole pieces and / or battery separators mentioned above, so that the transmission rate of active ions inside the battery can be significantly improved, so that it has excellent rate performance.
[0024] In some possible implementations, the electrochemical battery includes a lithium ion battery, a sodium ion battery, or a potassium ion battery.
[0025] In another aspect, a method for preparing a battery electrode sheet is provided. The battery electrode sheet is as described in any one of the above, and the method for preparing the battery electrode sheet comprises:
[0026] Providing a first dispersion, wherein the first dispersion includes a precursor of a fast ion material, wherein the precursor of the fast ion material is a precursor material capable of forming the fast ion material by lithiation, sodiumization or potassiumization;
[0027] Dispersing an active material, a conductive agent, and a binder in the first dispersion liquid to obtain a slurry;
[0028] The slurry is coated on a current collector and dried to obtain a pole piece intermediate;
[0029] The pole piece intermediate is subjected to lithium, sodium or potassium embedding treatment to obtain the battery pole piece.
[0030] By dispersing the active material, the conductive agent and the binder in the first dispersion containing the precursor of the fast ion material, the precursor of the fast ion material is evenly dispersed between the active material, the conductive agent and the binder to form a uniform slurry. After the slurry is applied to the current collector to form a pole piece intermediate, the active material and the conductive agent are bonded to the current collector through the binder and cooperate to form an electrode material layer. The precursor of the fast ion material will be in-situ filled in the gaps and surface of the electrode material layer, and a three-dimensional network structure will be formed accordingly based on the three-dimensional network gaps of the electrode material layer. According to the type of electrochemical cell, the pole piece intermediate is treated with lithium, sodium or potassium, so that the lithium element, sodium element or potassium element is combined with the precursor material of the fast ion material, thereby synthesizing a fast ion material suitable for lithium ion batteries, sodium ion batteries or potassium ion batteries accordingly, and the formed fast ion material is still in-situ filled in the gaps and surface of the electrode material layer, so as to prepare a battery pole piece with a stronger active ion migration rate.
[0031] In some possible implementations, the precursor of the fast ion material is selected from at least one of phosphorus sulfur compounds, silicon sulfur compounds, germanium sulfur compounds, tin sulfur compounds, silicon phosphorus compounds, germanium phosphorus compounds, tin phosphorus compounds, silicon phosphorus sulfur compounds, germanium phosphorus sulfur compounds, and tin phosphorus sulfur compounds.
[0032] In some possible implementations, providing a first dispersion includes:
[0033] Mixing and grinding a plurality of single-substance raw materials in sequence to obtain a mixed material, wherein the plurality of single-substance raw materials respectively correspond to a plurality of elements in the precursor of the fast ion material;
[0034] Sintering the mixed material to obtain a precursor of the fast ion material;
[0035] The precursor of the fast ion material is dispersed in a first solvent to obtain the first dispersion.
[0036] In some possible implementations, the operating conditions of the sintering process include at least one of the following conditions: vacuum atmosphere, inert environment, and sintering temperature of 300° C.-900° C., which can ensure that the chemical reaction is carried out to synthesize a precursor compound with a desired composition. The sintering time may be 6 h-24 h.
[0037] In another aspect, a method for preparing a battery separator is provided. The battery separator is as described in any one of the above, and the method for preparing the battery separator comprises:
[0038] Providing a second dispersion, wherein the second dispersion includes a plurality of different raw material compounds, wherein the plurality of different raw material compounds can generate fast ion materials through a chemical reaction;
[0039] Immersing the diaphragm body in the second dispersion, adding an excessive amount of the raw material compound with the lowest solubility among the multiple different raw material compounds to the second dispersion, so that the multiple different raw material compounds generate the fast ion material through a chemical reaction, and the fast ion material precipitates and adheres to the diaphragm body to obtain a wet diaphragm;
[0040] The wet separator is dried to obtain the battery separator.
[0041] The method for preparing a battery separator provided by an embodiment of the present disclosure is to immerse the separator body in a second dispersion containing a plurality of raw material compounds, and to add an excess of the raw material compound with the lowest solubility to the second dispersion until the dissolution limit of the fast ion material is reached. In this process, the fast ion material is generated based on the chemical reaction between a plurality of different raw material compounds, and the fast ion material is precipitated in situ in the separator body and uniformly attached to the separator body. The obtained wet separator is then dried to obtain a battery separator. Based on the three-dimensional network gaps of the separator body itself, the fast ion material after drying forms a three-dimensional network structure accordingly, thereby preparing a battery separator with excellent active ion migration rate.
[0042] In some possible implementations, the plurality of different raw material compounds include a first raw material compound and a second raw material compound;
[0043] The first raw material compound includes element A and element B, wherein element A is lithium, sodium or potassium, and element B is one of phosphorus, sulfur, silicon, germanium and tin;
[0044] The second raw material compound includes element C and element D, wherein element C and element D are each independently selected from one of phosphorus, sulfur, silicon, germanium, and tin.
[0045] In some possible implementations, the plurality of different raw material compounds further include a third raw material compound;
[0046] The third raw material compound includes element E and element F, wherein element E and element F are each independently selected from one of phosphorus, sulfur, silicon, germanium, and tin. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 A cross-sectional view of an exemplary battery electrode sheet provided in an embodiment of the present disclosure;
[0048] Figure 2 A schematic diagram of the structure of an exemplary electrochemical cell provided in an embodiment of the present disclosure;
[0049] Figure 3 A flowchart of preparing an exemplary battery electrode sheet provided in an embodiment of the present disclosure;
[0050] Figure 4 The Raman spectra of the electrode material layer of the button half-cell in Example 1 and Comparative Example 1;
[0051] Figure 5 This is the XPS-P2p spectrum of the electrode material layer of the negative electrode sheet of the lithium ion battery in Example 1;
[0052] Figure 6 This is the XPS-S2p spectrum of the electrode material layer of the negative electrode sheet of the lithium ion battery in Example 1;
[0053] Figure 7 The scanning electron microscope (SEM) image and the energy dispersive spectrometer (EDS) element distribution image of the surface of the electrode material layer of the negative electrode sheet of the lithium ion battery in Example 1;
[0054] Figure 8The SEM image and EDS element distribution diagram of the cross section of the electrode material layer of the negative electrode sheet of the lithium ion battery in Example 1;
[0055] Fig. 9 The first cycle charge and discharge curves of the button-type half-cells provided in Examples 1, 2, 3 and Comparative Example 1;
[0056] Fig.10 The charge and discharge curves of the button-type half-cells provided in Examples 1, 2, 3 and Comparative Example 1 at a current density of 1C;
[0057] Fig.11 Cyclic capacity curves of button-type half-cells provided for Example 4 and Comparative Example 2;
[0058] Fig.12 The cyclic coulombic efficiency curves of the button-type half-cells provided for Example 4 and Comparative Example 2 are shown.
[0059] The reference numerals represent:
[0060] 001, current collector; 002, electrode material layer;
[0061] 021. Active material; 022. Conductive agent; 023. Binder; 024. Fast ion material;
[0062] 100, positive electrode plate; 200, negative electrode plate; 300, electrolyte; 400, battery separator; 500, packaging layer. DETAILED DESCRIPTION
[0063] The following will be combined with the drawings in the embodiments of the present disclosure to clearly and completely describe the technical solutions in the embodiments of the present disclosure. Obviously, the described embodiments are part of the embodiments of the present disclosure, rather than all of the embodiments. Based on the embodiments in the present disclosure, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present disclosure.
[0064] At present, some common technical measures for arranging fast ion transport media in electrochemical cells are to set a fast ion transport material layer on the surface of the positive or negative electrode active material, physically add fast ion additives to the battery slurry, and coat the fast ion material layer on the surface of the battery pole piece and / or battery separator, etc. These solutions can only locally improve the ion conduction performance at the relevant position, so that the effect of improving the battery rate performance is limited.
[0065] On the one hand, the present disclosure provides a battery electrode, as shown in the attached Figure 1As shown, the battery pole piece includes a current collector 001 and an electrode material layer 002 located on the surface of the current collector 001; the electrode material layer 002 includes: an active material 021, a conductive agent 022, a binder 023 and a fast ion material 024, and the active material 021, the conductive agent 022 and the fast ion material 024 are combined by the binder 023 and integrally bonded to the current collector 001. The fast ion material 024 is distributed in the electrode material layer 002 in a three-dimensional network structure, and the fast ion material 024 is at least located in the internal gaps and the surface of the electrode material layer 002.
[0066] The electrode material layer 002 is formed by an active material 021, a conductive agent 022, a binder 023 and a fast ion material 024, and has a three-dimensional void inside. Multiple void segments in the three-dimensional void can be connected to each other or partially connected, and multiple voids extend from the inside of the electrode material layer 002 to the surface of the electrode material layer 002.
[0067] The existence of multiple gaps inside the electrode material layer 002 includes but is not limited to the following: gaps between different active materials, gaps between different conductive agents, gaps between active materials and conductive agents, gaps between active materials and binders, and gaps between conductive agents and binders.
[0068] The fast ion material is arranged in a three-dimensional network structure in the electrode material layer, and the fast ion material of the three-dimensional network structure is distributed in the entire area of the electrode material layer, so that it penetrates the electrode material layer along the first direction and the second direction, wherein the first direction is a direction parallel to the large surface of the current collector, and the second direction is a direction perpendicular to the large surface of the current collector. The "large surface" involved here refers to the surface of the current collector used to carry the electrode material layer.
[0069] In the disclosed embodiment, the fast ion material is located in the internal voids and surface of the electrode material layer. For example, the mass of the fast ion material located in the internal voids of the electrode material layer is 70%-99%, further 80%-99% of the total amount of the fast ion material.
[0070] For the three-dimensional network structure of the fast ion material, its corresponding microstructure is a network that runs through the three-dimensional voids of the electrode material layer and has spatial distribution continuity. The "running through" involved here means that the fast ion material exists in the observation area of 5μm*5μm (using field emission scanning electron microscope energy spectrum scanning sampling) at any position of the electrode material layer, so that the three-dimensional network structure of the fast ion material has spatial distribution continuity.
[0071] The battery pole piece provided by the embodiment of the present disclosure forms an electrode material layer by combining active materials, conductive agents and binders, and distributes fast ion materials in the electrode material layer in a three-dimensional network structure, and the fast ion materials in the three-dimensional network structure are located in the gaps and surface of the electrode material layer. In this way, the fast ion materials form a three-dimensional ion conductor medium network in the battery pole piece, and the three-dimensional ion conductor medium network has good uniformity and penetration characteristics, so that it can act on the entire area of the battery pole piece, and can improve the migration rate of active ions in the entire area of the battery pole piece, thereby releasing more of the fast charging and discharging capacity of the electrochemical cell under high-rate conditions, effectively improving the rate performance of the electrochemical cell, and especially can promote the electrochemical cell to obtain stronger rate performance under high-current conditions.
[0072] In the disclosed embodiment, the fast ion material fills the gaps and surface of the electrode material layer. Furthermore, the fast ion material is attached to the surface of at least one of the active material, the conductive agent and the binder. For example, the fast ion material is attached to the surfaces of the active material, the conductive agent and the binder.
[0073] The fast ion material is attached to the surface of the active material, the conductive agent and the binder, so that it is stably bonded to the electrode material layer, so that the electrode material layer has good structural stability. On the basis of stabilizing the structure of the electrode material layer, its ion conductivity is not inhibited, which is beneficial to improving the electrochemical performance and cycle life of the battery electrode.
[0074] The battery pole piece involved in the embodiments of the present disclosure can be used for various types of electrochemical batteries, and has strong versatility. These electrochemical batteries include but are not limited to lithium-ion batteries, sodium-ion batteries, potassium-ion batteries, all-solid-state batteries, etc. Of course, the battery pole piece can also be used for various types of supercapacitors.
[0075] One example is that the battery pole is used in a lithium-ion battery, and the fast ion material is at least one of a lithiated phosphorus-sulfur compound, a lithiated silicon-sulfur compound, a lithiated germanium-sulfur compound, a lithiated tin-sulfur compound, a lithiated silicon-phosphorus compound, a lithiated germanium-phosphorus compound, a lithiated tin-phosphorus compound, a lithiated silicon-phosphorus-sulfur compound, a lithiated germanium-phosphorus-sulfur compound, and a lithiated tin-phosphorus-sulfur compound.
[0076] Phosphorus-sulfur compounds, silicon-sulfur compounds, germanium-sulfur compounds, tin-sulfur compounds, silicon-phosphorus compounds, germanium-phosphorus compounds, tin-phosphorus compounds, silicon-phosphorus-sulfur compounds, germanium-phosphorus-sulfur compounds, and tin-phosphorus-sulfur compounds are all ion conductors. When battery electrodes are used in lithium-ion batteries, these compounds are further subjected to lithium treatment to further contain lithium elements, making these fast ion materials good conductors of lithium ions and significantly improving the migration rate of lithium ions.
[0077] The following describes the general chemical formulas of lithiated phosphorus sulfur compounds, lithiated silicon sulfur compounds, lithiated germanium sulfur compounds, lithiated tin sulfur compounds, lithiated silicon phosphorus compounds, lithiated germanium phosphorus compounds, lithiated tin phosphorus compounds, lithiated silicon phosphorus sulfur compounds, lithiated germanium phosphorus sulfur compounds, and lithiated tin phosphorus sulfur compounds. The x and y involved in the general chemical formulas of the above compounds are the atomic percentages of the corresponding elements, and the chemical formulas of the compounds can be determined accordingly based on the atomic percentages of the elements.
[0078] When the fast ion material is a lithiated material, its general chemical formula is Li (1-x-y-z) A x B y C z , wherein the A element, the B element and the C element are different and are selected from phosphorus, silicon, germanium, tin and sulfur. x, y and z are the atomic percentages of the corresponding elements, wherein 0<x<1, 0<y<1, 0≤z<1, and further, 0.01<x<0.9, 0.01<y<0.9, 0≤z<0.9.
[0079] For example, for lithiated phosphorus-sulfur compounds, the general chemical formula may be Li (1-x-y) P x S y , wherein the atomic percentage x ranges from 0.05<x<0.5, and the atomic percentage y ranges from 0.3<y<0.9. For example, this includes but is not limited to Li3PS4 and the like.
[0080] For lithiated germanium phosphorus sulfide, the general chemical formula can be Li (1-x-y-z) Ge x P y S z , where the atomic percentage x ranges from 0.05 < x < 0.3, the atomic percentage y ranges from 0.05 < y < 0.25, and the atomic percentage z ranges from 0.1 < y < 0.9. For example, this includes but is not limited to Li 10 GeP2S 12 wait.
[0081] Another example is that the battery pole is used in a sodium ion battery, and the fast ion material is at least one of sodium-containing phosphorus-sulfur compounds, sodium-containing silicon-sulfur compounds, sodium-containing germanium-sulfur compounds, sodium-containing tin-sulfur compounds, sodium-containing silicon-phosphorus compounds, sodium-containing germanium-phosphorus compounds, sodium-containing tin-phosphorus compounds, sodium-containing silicon-phosphorus-sulfur compounds, sodium-containing germanium-phosphorus-sulfur compounds, and sodium-containing tin-phosphorus-sulfur compounds.
[0082] Phosphorus-sulfur compounds, silicon-sulfur compounds, germanium-sulfur compounds, tin-sulfur compounds, silicon-phosphorus compounds, germanium-phosphorus compounds, tin-phosphorus compounds, silicon-phosphorus-sulfur compounds, germanium-phosphorus-sulfur compounds, and tin-phosphorus-sulfur compounds are all ion conductors. When battery electrodes are used in sodium-ion batteries, these compounds are further treated with sodium to further contain sodium elements, making these fast ion materials good conductors of sodium ions and significantly improving the migration rate of sodium ions.
[0083] The following describes the general chemical formulas of sodium phosphorus sulfur compounds, sodium silicon sulfur compounds, sodium germanium sulfur compounds, sodium tin sulfur compounds, sodium silicon phosphorus compounds, sodium germanium phosphorus compounds, sodium tin phosphorus compounds, sodium silicon phosphorus sulfur compounds, sodium germanium phosphorus sulfur compounds, and sodium tin phosphorus sulfur compounds. The x and y involved in the general chemical formulas of the above compounds are the atomic percentages of the corresponding elements, and the chemical formulas of the compounds can be determined accordingly based on the atomic percentages of the elements.
[0084] When the fast ion material is a sodium material, its general chemical formula is Na (1-x-y-z) A x B y C z , wherein the A element, the B element and the C element are different and are selected from phosphorus, silicon, germanium, tin and sulfur. x, y and z are the atomic percentages of the corresponding elements, wherein 0<x<1, 0<y<1, 0≤z<1, and further, 0.01<x<0.9, 0.01<y<0.9, 0≤z<0.9.
[0085] Another example is that the battery electrode is used in a potassium ion battery, and the fast ion material is at least one of a potassium-containing phosphorus-sulfur compound, a potassium-containing silicon-sulfur compound, a potassium-containing germanium-sulfur compound, a potassium-containing tin-sulfur compound, a potassium-containing silicon-phosphorus compound, a potassium-containing germanium-phosphorus compound, a potassium-containing tin-phosphorus compound, a potassium-containing silicon-phosphorus-sulfur compound, a potassium-containing germanium-phosphorus-sulfur compound, and a potassium-containing tin-phosphorus-sulfur compound.
[0086] Phosphorus-sulfur compounds, silicon-sulfur compounds, germanium-sulfur compounds, tin-sulfur compounds, silicon-phosphorus compounds, germanium-phosphorus compounds, tin-phosphorus compounds, silicon-phosphorus-sulfur compounds, germanium-phosphorus-sulfur compounds, and tin-phosphorus-sulfur compounds are all ion conductors. When battery electrodes are used in potassium-ion batteries, these compounds are further potassiumized to further contain potassium elements, making these fast ion materials good conductors of potassium ions and significantly improving the migration rate of potassium ions.
[0087] The following describes the general chemical formulas of potassium-phosphorus-sulfur compounds, potassium-silicon-sulfur compounds, potassium-germanium-sulfur compounds, potassium-tin-sulfur compounds, potassium-silicon-phosphorus compounds, potassium-germanium-phosphorus compounds, potassium-tin-phosphorus compounds, potassium-silicon-phosphorus-sulfur compounds, potassium-germanium-phosphorus-sulfur compounds, and potassium-tin-phosphorus-sulfur compounds. The x and y involved in the general chemical formulas of the above compounds are the atomic percentages of the corresponding elements, and the chemical formulas of the compounds can be determined accordingly based on the atomic percentages of the elements.
[0088] When the fast ion material is a potassium material, its general chemical formula is K (1-x-y-z) A x B y C z , wherein the A element, the B element and the C element are different and are selected from phosphorus, silicon, germanium, tin and sulfur. x, y and z are the atomic percentages of the corresponding elements, wherein 0<x<1, 0<y<1, 0≤z<1, and further, 0.01<x<0.9, 0.01<y<0.9, 0≤z<0.9.
[0089] In some examples, the mass ratio of active material, conductive agent and binder is 90-95:0.1-10:1-10, wherein the weight parts of active material include but are not limited to 90 parts, 91 parts, 92 parts, 93 parts, 94 parts, 95 parts, etc., the weight parts of conductive agent include but are not limited to 0.5 parts, 1 parts, 2 parts, 3 parts, 3 parts, 4 parts, 5 parts, 5.5 parts, 6 parts, 6.5 parts, 7 parts, 7.5 parts, 8 parts, 8.5 parts, 9 parts, 10 parts, etc., and the weight parts of binder include but are not limited to 1 part, 2 parts, 3 parts, 3 parts, 4 parts, 5 parts, 5.5 parts, 6 parts, 6.5 parts, 7 parts, 7.5 parts, 8 parts, 8.5 parts, 9 parts, 9.5 parts, 10 parts, etc.
[0090] In some examples, the mass of the fast ion material is 0.1%-20% of the total mass of the electrode material layer, including but not limited to 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, etc. The mass of the fast ion material is within the above range to ensure that it can be evenly distributed in the gaps and surfaces of the entire area of the electrode material layer.
[0091] The current collector contained in the battery electrode can be made of metal foil, conductive carbon material, etc., including but not limited to: copper foil, copper mesh, carbon-coated copper foil, aluminum foil, nickel foil, composite metal foil, carbon paper, conductive carbon cloth, etc.
[0092] For the active material contained in the electrode material layer, when the battery pole piece is used as a negative electrode pole piece, its active material is a negative electrode active material, and the negative electrode active material includes but is not limited to: natural graphite, artificial graphite, graphene, carbon nanotubes, soft carbon, hard carbon, silicon oxide, silicon carbon material, lithium titanate, etc.
[0093] When the battery electrode is used as a positive electrode, its active material is a positive electrode active material. The positive electrode active material may be different for different battery types, which are exemplified below.
[0094] When the battery pole piece is used in a lithium-ion battery, the positive electrode active material includes but is not limited to: at least one of lithium iron phosphate, lithium iron manganese phosphate, lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt manganese oxide, and lithium-rich layered oxide. Among them, the chemical formula of lithium nickel cobalt manganese oxide is LiMO2, where M is a nickel cobalt manganese ternary compound, and the atomic percentages of nickel, cobalt and manganese can be any ratio, for example, the atomic percentage of nickel is 82%, the atomic percentage of cobalt is 9%, and the atomic percentage of manganese is 9%.
[0095] When the battery pole piece is used in a sodium ion battery, the positive electrode active material includes but is not limited to: oxides (layered structure and tunnel structure), polyanion compounds, Prussian blue, etc., the layered oxides may be, for example, sodium iron manganate, sodium iron titanate, etc., the polyanion compounds may be, for example, sodium iron sulfate, sodium iron phosphate, sodium vanadium phosphate, sodium vanadium fluorophosphate, pyrophosphate composite polyanion compounds, etc.
[0096] When the battery pole piece is used in a potassium ion battery, the positive electrode active material includes but is not limited to: layered metal oxides, polyanion compounds, Prussian blue, etc., wherein the chemical formula of the layered metal oxide can be K x MO2, where M can be Fe, Mn, Co, etc., and the chemical formula of the polyanion compound can be KM x (XO4) y , where M can be Fe, Mn, Co, etc.
[0097] The conductive agent contained in the electrode material layer includes, but is not limited to, one or more of acetylene black, graphite, carbon black, carbon nanotubes, and conductive carbon fibers.
[0098] The binder contained in the electrode material layer includes, but is not limited to, styrene-butadiene rubber-carboxymethyl cellulose (SBR-CMC for short), nitrile rubber, polyvinylidene fluoride, polytetrafluoroethylene, polyvinyl alcohol, polyacrylonitrile, polyacrylic acid, polyacrylate, and the like.
[0099] On the other hand, an embodiment of the present disclosure provides a battery separator, which includes a separator body and a fast ion material, wherein the fast ion material is distributed in the separator body in a three-dimensional network structure, and the fast ion material is at least located in the gaps and surface of the separator body.
[0100] The "membrane body" involved in the embodiments of the present disclosure may be a currently known battery membrane, including but not limited to: polyethylene membrane, polypropylene membrane, polyvinylidene fluoride membrane, copolymer membrane of propylene and ethylene, cellulose composite membrane, etc. It can be seen that the membrane body itself is a porous structure, which has voids in a three-dimensional network structure.
[0101] The fast ion material is arranged in a three-dimensional network structure in the diaphragm body, and the fast ion material of the three-dimensional network structure is distributed in the entire area of the diaphragm body, so that it penetrates the diaphragm body in both the first direction and the second direction, wherein the first direction is a direction parallel to the large surface of the diaphragm body, and the second direction is a direction perpendicular to the large surface of the diaphragm body. The "large surface" involved here refers to the surface of the diaphragm body facing the battery pole piece.
[0102] In the disclosed embodiment, the fast ion material is located in the gaps and surface of the diaphragm body. For example, the mass of the fast ion material located in the internal gaps of the diaphragm body is 70%-99%, further 80%-99% of the total amount of the fast ion material.
[0103] The three-dimensional network structure of the fast ion material has a microstructure that is a network that runs through the three-dimensional voids of the separator body and has spatial distribution continuity. The "running through" involved here means that the fast ion material exists in the observation area of 5μm*5μm (using field emission scanning electron microscope energy spectrum scanning sampling) at any position of the battery separator, so that the three-dimensional network structure of the fast ion material has spatial distribution continuity.
[0104] The battery diaphragm provided by the embodiment of the present disclosure makes the fast ion material distributed in the gaps and surface of the diaphragm body in a three-dimensional network structure. In this way, the fast ion material forms a three-dimensional ion conductor medium network in the diaphragm body. The three-dimensional ion conductor medium network has good uniformity and penetration characteristics, so that it can act on the entire area of the diaphragm body, and can improve the migration rate of active ions in the entire area of the diaphragm body, thereby facilitating the rapid release of the charge and discharge capacity of the electrochemical battery under high-rate conditions, effectively improving the rate performance of the electrochemical battery, and especially promoting the electrochemical battery to obtain stronger rate performance under high-current conditions.
[0105] The battery separator involved in the embodiments of the present disclosure can be used for various types of electrochemical batteries and has strong versatility. These electrochemical batteries include but are not limited to lithium-ion batteries, sodium-ion batteries, potassium-ion batteries, all-solid-state batteries, etc. Of course, the battery separator can also be used for various types of supercapacitors.
[0106] One example is that the battery separator is used in a lithium-ion battery, and the fast ion material is at least one of a lithiated phosphorus sulfur compound, a lithiated silicon sulfur compound, a lithiated germanium sulfur compound, a lithiated tin sulfur compound, a lithiated silicon phosphorus compound, a lithiated germanium phosphorus compound, a lithiated tin phosphorus compound, a lithiated silicon phosphorus sulfur compound, a lithiated germanium phosphorus sulfur compound, and a lithiated tin phosphorus sulfur compound.
[0107] Another example is that the battery separator is used in a sodium ion battery, and the fast ion material is at least one of a sodium-containing phosphorus-sulfur compound, a sodium-containing silicon-sulfur compound, a sodium-containing germanium-sulfur compound, a sodium-containing tin-sulfur compound, a sodium-containing silicon-phosphorus compound, a sodium-containing germanium-phosphorus compound, a sodium-containing tin-phosphorus compound, a sodium-containing silicon-phosphorus-sulfur compound, a sodium-containing germanium-phosphorus-sulfur compound, and a sodium-containing tin-phosphorus-sulfur compound.
[0108] Another example is that the battery separator is used in a potassium ion battery, and the fast ion material is at least one of a potassium-containing phosphorus-sulfur compound, a potassium-containing silicon-sulfur compound, a potassium-containing germanium-sulfur compound, a potassium-containing tin-sulfur compound, a potassium-containing silicon-phosphorus compound, a potassium-containing germanium-phosphorus compound, a potassium-containing tin-phosphorus compound, a potassium-containing silicon-phosphorus-sulfur compound, a potassium-containing germanium-phosphorus-sulfur compound, and a potassium-containing tin-phosphorus-sulfur compound.
[0109] Among them, the various types of fast ion materials involved above can refer to the various types of fast ion materials described in the above-mentioned battery electrode, and will not be repeated here.
[0110] For the battery separator provided by the embodiment of the present disclosure, the mass of the fast ion material is 0.1%-20% of the total mass of the battery separator, including but not limited to 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, etc. The mass of the fast ion material is within the above range, which can ensure that it can be evenly distributed in the gaps and surfaces of the entire area of the separator body.
[0111] On the other hand, an embodiment of the present disclosure further provides an electrochemical cell, which includes at least one of any of the above-mentioned battery pole sheets and any of the above-mentioned battery separators.
[0112] The electrochemical cell provided in the embodiments of the present disclosure is also a secondary battery, which has all the advantages of the battery pole pieces and / or battery separators mentioned above, so that the transmission rate of active ions inside the battery can be significantly improved, so that it has excellent rate performance.
[0113] As attached Figure 2As shown, the electrochemical cell includes a positive electrode sheet 100, a negative electrode sheet 200, an electrolyte 300, a battery separator 400 and a packaging layer 500. The electrolyte 300 is filled in the space between the positive electrode sheet 100 and the negative electrode sheet 200, and the battery separator 400 is located in the electrolyte 300 to isolate the positive electrode sheet 100 from the negative electrode sheet 200. The packaging layer 500 is used to package the positive electrode sheet 100, the negative electrode sheet 200, the electrolyte 300 and the battery separator 400 as a whole.
[0114] Among them, at least one of the positive electrode sheet 100, the negative electrode sheet 200, and the battery separator 400 adopts the corresponding battery electrode sheet or battery separator provided in the embodiment of the present disclosure, which includes but is not limited to: the positive electrode sheet 100 adopts the positive battery electrode sheet provided in the embodiment of the present disclosure; the negative electrode sheet 200 adopts the negative battery electrode sheet provided in the embodiment of the present disclosure; the battery separator 400 adopts the battery separator provided in the embodiment of the present disclosure; the positive electrode sheet 100 and the negative electrode sheet 200 respectively adopt the positive battery electrode sheet and the negative electrode sheet provided in the embodiment of the present disclosure. Battery pole pieces; the positive pole piece 100 adopts the positive battery pole piece provided in the embodiment of the present disclosure, and the battery separator 400 adopts the battery separator provided in the embodiment of the present disclosure; the negative pole piece 200 adopts the negative battery pole piece provided in the embodiment of the present disclosure, and the battery separator 400 adopts the battery separator provided in the embodiment of the present disclosure; the positive pole piece 100 and the negative pole piece 200 respectively adopt the positive battery pole piece and the negative battery pole piece provided in the embodiment of the present disclosure, and the battery separator 400 adopts the battery separator provided in the embodiment of the present disclosure.
[0115] In some examples, the electrochemical batteries involved in the embodiments of the present disclosure include but are not limited to lithium ion batteries, sodium ion batteries, potassium ion batteries, etc. The lithium ion batteries, sodium ion batteries, and potassium ion batteries involved above can be aqueous batteries or organic batteries.
[0116] On the other hand, the embodiments of the present disclosure further provide a method for preparing a battery electrode sheet, wherein the battery electrode sheet is as described above, and the method for preparing the battery electrode sheet comprises:
[0117] Step S11, providing a first dispersion liquid, wherein the first dispersion liquid includes a precursor of a fast ion material, wherein the precursor of the fast ion material is a precursor material that can form a fast ion material through lithiation, sodiumization or potassiumization.
[0118] Step S12: dispersing the active material, the conductive agent and the binder in the first dispersion liquid to obtain a slurry.
[0119] Step S13, coating the slurry on the current collector, and drying to obtain a pole piece intermediate (reference Figure 3 Part A-Part B of the .
[0120] Step S14: insert lithium, sodium or potassium into the electrode intermediate to obtain a battery electrode (reference Figure 3 of the FDA).
[0121] The method for preparing a battery pole piece provided by the embodiment of the present disclosure disperses the active material, the conductive agent and the binder in a first dispersion containing a precursor of a fast ion material, so that the precursor of the fast ion material is evenly dispersed between the active material, the conductive agent and the binder to form a uniform slurry. After the slurry is applied to the current collector to form a pole piece intermediate, the active material and the conductive agent are bonded to the current collector through the binder and cooperate to form an electrode material layer, and the precursor of the fast ion material is in situ filled in the internal voids and surface of the electrode material layer, and a three-dimensional network structure is formed accordingly based on the three-dimensional network voids of the electrode material layer. According to the type of electrochemical cell, the pole piece intermediate is treated with lithium, sodium or potassium, so that the lithium element, sodium element or potassium element is combined with the precursor material of the fast ion material, thereby synthesizing a fast ion material suitable for lithium ion batteries, sodium ion batteries or potassium ion batteries accordingly, and the formed fast ion material is still in situ filled in the internal voids and surface of the electrode material layer, so as to prepare a battery pole piece with a stronger active ion migration rate.
[0122] The following further describes the various steps and functions involved in the battery electrode.
[0123] For step S11, a first dispersion is provided, wherein the first dispersion includes a precursor of a fast ion material, wherein the precursor of the fast ion material is a precursor material that can form a fast ion material through lithiation, sodiumization, or potassiumization.
[0124] Exemplarily, the precursor of the fast ion material is selected from at least one of phosphorus-sulfur compounds, silicon-sulfur compounds, germanium-sulfur compounds, tin-sulfur compounds, silicon-phosphorus compounds, germanium-phosphorus compounds, tin-phosphorus compounds, silicon-phosphorus-sulfur compounds, germanium-phosphorus-sulfur compounds, and tin-phosphorus-sulfur compounds. The composition of these compounds is described above with respect to the relevant compounds in the battery pole piece, and will not be repeated here.
[0125] The first dispersion includes a first solvent and a precursor of a fast ion material. The first solvent may be an organic solvent such as N-methyl-pyrrolidone (NMP), tetrahydrofuran, acetonitrile, or an inorganic solvent such as ultrapure water.
[0126] In order to achieve uniform dispersion of the precursor containing fast ion material, active material, conductive agent and binder in the first dispersion, the concentration of the precursor containing fast ion material in the first dispersion can be 0.5 mg / ml-10 mg / mL, and further can be 1 mg / ml-5 mg / mL, for example, this includes but is not limited to 1 mg / ml, 1.5 mg / ml, 2 mg / ml, 2.5 mg / ml, 3 mg / ml, 3.5 mg / ml, 4 mg / ml, 4.5 mg / ml, 5 mg / ml, etc.
[0127] In some examples, providing a first dispersion liquid involved in step S11 also includes: mixing and grinding a plurality of single-element raw materials in sequence to obtain a mixed material, wherein the plurality of single-element raw materials respectively correspond to a plurality of elements in a precursor of a fast ion material; sintering the mixed material to obtain a precursor of a fast ion material; and dispersing the precursor of the fast ion material in a first solvent to obtain a first dispersion liquid.
[0128] Exemplarily, the precursor of the fast ion material is selected from at least one of phosphorus sulfur compounds, silicon sulfur compounds, germanium sulfur compounds, tin sulfur compounds, silicon phosphorus compounds, germanium phosphorus compounds, tin phosphorus compounds, silicon phosphorus sulfur compounds, germanium phosphorus sulfur compounds, and tin phosphorus sulfur compounds. Then, the corresponding single substance raw materials are phosphorus + sulfur, silicon + sulfur, germanium + sulfur, tin + sulfur, silicon + phosphorus, germanium + phosphorus, tin + phosphorus, silicon + phosphorus + sulfur, germanium + phosphorus + sulfur, tin + phosphorus + sulfur.
[0129] The amount (i.e., molar ratio) of the above-mentioned single raw materials is determined according to the atomic percentage of each element in the fast ion material, and the content of the doped lithium, sodium or potassium element is determined by controlling the lithiation potential, sodium potential or potassium potential.
[0130] In some examples, the multiple single material materials are in powder form, for example, with a particle size of micro-nano scale, and are ground into micro-nano scale mixed materials, so that the multiple single material materials are evenly mixed and sufficient contact between each single material material is achieved.
[0131] By sintering the mixed material, the multiple single raw materials undergo bond breaking and recombination to achieve stable chemical bonding, thereby synthesizing the precursor of the fast ion material in the form of a compound. Since the multiple single raw materials are in powder form, the precursor of the fast ion material formed is also in powder form.
[0132] In some examples, the operating conditions of the sintering process include at least one of the following conditions: vacuum atmosphere, inert environment, and sintering temperature of 300° C.-900° C. In this way, it is possible to ensure that the chemical reaction is carried out to synthesize a precursor compound with a desired composition. The sintering time may be 6 hours to 24 hours.
[0133] Among them, the vacuum atmosphere can be provided by vacuum equipment such as a vacuum furnace, the inert environment can be an argon atmosphere, and the sintering temperature includes but is not limited to 300℃, 350℃, 400℃, 450℃, 500℃, 550℃, 600℃, 650℃, 700℃, 750℃, 800℃, 850℃, 900℃, etc.
[0134] For step S12, the active material, the conductive agent and the binder are dispersed in the first dispersion to obtain a slurry, wherein the solid content of the slurry is 40%-75%, and can further be 45%-52%. The solid content of the slurry within this range is conducive to coating and forming a film on the current collector.
[0135] For step S14, the pole piece intermediate is subjected to lithium, sodium or potassium intercalation treatment to obtain a battery pole piece. This includes: assembling a battery using the pole piece intermediate, charging and discharging the battery, and intercalating lithium, sodium or potassium into a precursor of a fast ion material based on an electrochemical reaction. The battery can be a half-battery or a full-battery.
[0136] For half-cells, the battery pole piece and the corresponding metal electrode can form a button half-cell. For full-cells, the battery pole piece and the corresponding commercial positive electrode or negative electrode can be combined to form an Ah-level soft-pack full-cell. The above-mentioned lithium, sodium or potassium intercalation refers to the lithium, sodium or potassium intercalation of the negative electrode during the first cycle of the half-cell or full-cell.
[0137] After the lithium, sodium or potassium embedding is completed, the battery can be disassembled and the battery electrode can be taken out to obtain the battery electrode product. Of course, the battery can also be made into a final battery product. In this way, after the first cycle of the battery product, the battery electrode can be prepared at the same time.
[0138] In some embodiments, the preparation steps of the battery pole piece are as follows: a plurality of single raw materials for preparing a precursor of a fast ion material are mixed according to a set molar ratio, and a mixed material is obtained after mechanical ball milling. The mixed material is placed in a tubular vacuum furnace for sintering treatment to obtain a precursor of a fast ion material. A set amount of the precursor of the fast ion material is dispersed in a first solvent, and a first dispersion is obtained after stirring. The active material, the conductive agent and the binder are dispersed in the first dispersion, and a slurry is obtained after stirring. The slurry is applied to the current collector, and a pole piece intermediate is obtained after drying treatment (the drying temperature can be 45°C-60°C) and rolling treatment. The pole piece intermediate is assembled to form a battery, and the battery is subjected to lithium, sodium or potassium embedding treatment to obtain a battery pole piece.
[0139] In another aspect, the present disclosure also provides a method for preparing a battery separator. The battery separator is as described above, and the method for preparing the battery separator includes:
[0140] Step S21 : providing a second dispersion liquid, wherein the second dispersion liquid includes a plurality of different raw material compounds, and the plurality of different raw material compounds can generate fast ion materials through chemical reactions.
[0141] Step S22, immersing the diaphragm body in the second dispersion, adding an excessive amount of the raw material compound with the lowest solubility among the multiple different raw material compounds to the second dispersion, so that the multiple different raw material compounds generate fast ion materials through chemical reactions, and the fast ion materials precipitate and adhere to the diaphragm body to obtain a wet diaphragm.
[0142] Step S23, drying the wet separator to obtain a battery separator.
[0143] The method for preparing a battery separator provided by an embodiment of the present disclosure is to immerse the separator body in a second dispersion containing a plurality of raw material compounds, and to add an excess of the raw material compound with the lowest solubility to the second dispersion until the dissolution limit of the fast ion material is reached. In this process, the fast ion material is generated based on the chemical reaction between a plurality of different raw material compounds, and the fast ion material is precipitated in situ in the separator body and uniformly attached to the separator body. The obtained wet separator is then dried to obtain a battery separator. Based on the three-dimensional network gaps of the separator body itself, the fast ion material after drying forms a three-dimensional network structure accordingly, thereby preparing a battery separator with excellent active ion migration rate.
[0144] For step S21 , the second dispersion liquid includes a second solvent and a plurality of different raw material compounds dispersed in the second solvent, and the plurality of different raw material compounds includes at least a first raw material compound and a second raw material compound.
[0145] The first raw material compound includes element A and element B. The chemical formula of the first raw material compound is A x B y , wherein x and y are both atomic percentages, x+y=1, element A is lithium, sodium or potassium, and element B is one of phosphorus, sulfur, silicon, germanium and tin.
[0146] The second raw material compound includes C element and D element. The chemical formula of the second raw material compound is C x D y , wherein x and y are both atomic percentages, x+y=1, and the C element and the D element are each independently selected from one of phosphorus, sulfur, silicon, germanium, and tin.
[0147] Furthermore, the plurality of different raw material compounds include at least a third raw material compound, the third raw material compound is different from the second raw material compound, the third raw material compound includes an E element and an F element, and the chemical formula of the third raw material compound is E x F y , wherein x and y are both atomic percentages, x+y=1, and the E element and the F element are each independently selected from one of phosphorus, sulfur, silicon, germanium, and tin.
[0148] In some examples, the mass percentage of the first raw material compound in the second dispersion in step S21 is 1%-50%, and further can be 10%-20%.
[0149] The various raw material compounds can be selected so that they can generate fast ion materials with desired chemical compositions based on chemical reactions. The following are examples:
[0150] When the fast ion material is a lithiated phosphorus-sulfur compound, the multiple different raw material compounds may include a first raw material compound and a second raw material compound, the first raw material compound is a lithium-sulfur compound (such as Li2S), and the second raw material compound is a phosphorus-sulfur compound (such as P2S5, P4S3, P2S3, P4S7, etc.).
[0151] When the fast ion material is a lithiated silicon-sulfur compound, the plurality of different raw material compounds may include a first raw material compound and a second raw material compound, the first raw material compound being a lithium-sulfur compound (eg, Li2S) and the second raw material compound being a silicon-sulfur compound (eg, SiS2).
[0152] When the fast ion material is a lithiated silicon-phosphorus-sulfur compound, the multiple different raw material compounds may include a first raw material compound, a second raw material compound and a third raw material compound. The first raw material compound is a lithium-sulfur compound (such as Li2S), the second raw material compound is a phosphorus-sulfur compound (such as P2S5, P4S3, P2S3, P4S7, etc.), and the third raw material compound is a silicon-sulfur compound (such as SiS2) or a silicon-phosphorus compound (such as SiP4), etc.
[0153] The above raw material compounds can all be in powder form to achieve uniform dispersion and ensure sufficient contact between each other. For example, the particle size of each of the above raw material compounds can be micro-nano particle size.
[0154] The second solvent involved in step S21 includes, but is not limited to, at least one of tetrahydrofuran, acetonitrile, dimethyl ether, diethyl ether, methyl acetate, ethyl acetate, and butyl acetate, all of which are inert solvents and can achieve the dissolution and dispersion of the raw material compound. For example, tetrahydrofuran or acetonitrile can be used as the second solvent.
[0155] For step S22, the diaphragm body is immersed in the second dispersion, and the raw material compound with the lowest solubility among multiple different raw material compounds is excessively added to the second dispersion, so that the multiple different raw material compounds generate fast ion materials through chemical reactions, and the fast ion materials are precipitated and attached to the diaphragm body to obtain a wet diaphragm.
[0156] The raw material compound with the worst solubility in the second solvent is selected from a plurality of different raw material compounds, and is added excessively to the second dispersion to promote and accelerate the chemical reaction between the plurality of raw material compounds, so that the fast ion material is saturated and precipitated. For example, the first raw material compound is usually the raw material compound with the worst solubility.
[0157] In some examples, the molar amount of the raw material compound with the lowest solubility added in excess is made to meet the following conditions: ensuring that the dissolution limit of the fast ion material is reached, so that the molar amounts of the various different raw material compounds can ultimately meet the stoichiometric ratio of the synthesized fast ion material, thereby allowing the fast ion material to react and be produced smoothly and precipitated in situ.
[0158] In step S23, the wet diaphragm is dried to obtain a battery diaphragm. In order to prevent the drying process from damaging the diaphragm body, the wet diaphragm is dried under the following operating conditions: vacuum atmosphere, drying temperature of 50°C-80°C. For example, the wet diaphragm is dried at 50°C-80°C for 1-12 hours in a vacuum oven.
[0159] For example, the drying temperature includes but is not limited to 50° C., 52° C., 55° C., 57° C., 59° C., 60° C., 62° C., 65° C., 67° C., 69° C., 70° C., 73° C., 75° C., 78° C., 79° C., etc. The drying time includes but is not limited to 3 hours, 4 hours, 5 hours, 6 hours, etc.
[0160] The specific embodiments of the present disclosure will be described in more detail below. Although the specific embodiments of the present disclosure are described below, it should be understood that the present disclosure can be implemented in various forms and should not be limited by the embodiments set forth herein. If specific techniques or conditions are not specified in the examples, they are carried out according to the techniques or conditions described in the literature in this area or according to the product specifications. If the manufacturers of reagents or instruments are not specified, they are all conventional products that can be obtained commercially.
[0161] Example 1
[0162] This embodiment 1 provides a lithium-ion battery negative electrode sheet, which includes a current collector and an electrode material layer located on the surface of the current collector; the electrode material layer includes: an active material, a conductive agent, a binder and a fast ion material, the active material, the conductive agent and the fast ion material are combined by the binder and integrally bonded to the current collector, the fast ion material is distributed in the electrode material layer in a three-dimensional network structure, and the fast ion material is located in the internal gaps and surface of the electrode material layer. Among them, the active material is a commercial graphite negative electrode material, the conductive agent is acetylene black, the binder is styrene-butadiene rubber-carboxymethyl cellulose, and the fast ion material is a lithiated phosphorus-sulfur compound (Li3PS4).
[0163] The preparation method of the negative electrode sheet of the lithium ion battery is as follows:
[0164] Sulfur powder and red phosphorus powder were mixed in a molar ratio of 4:1, and mechanically ball-milled (using 5 mm diameter zirconium oxide beads, the mass ratio of zirconium beads to the mixed powder of sulfur powder and red phosphorus powder was 10:1, the ball-milling time was 15 min, and the rotation speed was 1500 rpm) to obtain a mixed material. The mixed material was transferred to a vacuum furnace protected by high-purity argon gas and sintered at 300 ° C for 12 hours to obtain a phosphorus-sulfur compound (P4S 16 ).
[0165] The phosphorus-sulfur compound obtained by sintering was dispersed in N-methyl-pyrrolidone solvent and fully stirred (stirred at 500 rpm for 30 min) to dissolve to form a first dispersion liquid. The concentration of the phosphorus-sulfur compound in the first dispersion liquid was 5 mg / mL.
[0166] A negative electrode material is provided, the negative electrode material comprising commercial graphite negative electrode material, acetylene black, styrene butadiene rubber-carboxymethyl cellulose in a mass ratio of 95:0.3:4.7, wherein the mass ratio of styrene butadiene rubber to carboxymethyl cellulose is 3.2:1.5. The negative electrode material is mixed and dispersed in the first dispersion, and stirred thoroughly (stirred at 1000 rpm for 10 min) to obtain a slurry. Among them, the mass of the phosphorus-sulfur compound is 3% of the total mass of the phosphorus-sulfur compound and the negative electrode material (hereinafter referred to as the composite mass percentage of the phosphorus-sulfur compound), and the solid content of the slurry is 50%. The slurry is coated on a carbon-coated copper foil, and dried in a vacuum oven at 80°C for 6 hours to obtain a pole piece intermediate.
[0167] One way is to use the pole piece intermediate as the working electrode, the battery lithium sheet as the counter electrode, the electrolyte as 1 mol / LLiPF6 (ethylene carbonate EC + propylene carbonate PC + low viscosity diethyl carbonate DEC + ethyl methyl carbonate EMC, the volume ratio of the four is 1:0.3:1:1), and the battery separator is a single-layer polyethylene film, so as to assemble a button half-cell.
[0168] Another way is to use the electrode intermediate and the commercial NCM622 ternary positive electrode to prepare the electrode sheet, and make the electrolyte 1 mol / LLiPF6 (EC+PC+DEC+EMC, the volume ratio of the four is 1:0.3:1:1), and the battery separator is a three-layer composite separator of polypropylene film / polyethylene film / polypropylene film, so as to assemble Ah-level soft-pack batteries.
[0169] The button half-cell and Ah-level soft-pack battery prepared above are both lithium-intercalated to a potential of 5 mV, so that the phosphorus-sulfur compound in the electrode intermediate is fully lithium-intercalated, and the lithiated phosphorus-sulfur compound Li3PS4 is synthesized, thereby obtaining a lithium-ion battery negative electrode accordingly.
[0170] Example 2
[0171] This embodiment 2 provides a lithium ion battery negative electrode sheet and a button half-cell based on the lithium ion battery negative electrode sheet, and the preparation method thereof is the same as the preparation method of the lithium ion battery negative electrode sheet and the button half-cell in embodiment 1, the only difference being that the composite mass percentage of the phosphorus-sulfur compound is adjusted to 5%.
[0172] Example 3
[0173] This embodiment 3 provides a lithium ion battery negative electrode sheet and a button half-cell based on the lithium ion battery negative electrode sheet, and the preparation method thereof is the same as the preparation method of the lithium ion battery negative electrode sheet and the button half-cell in embodiment 1, the only difference being that the composite mass percentage of the phosphorus-sulfur compound is adjusted to 10%.
[0174] Comparative Example 1
[0175] Comparative Example 1 provides a lithium ion battery negative electrode sheet and a button half-cell based on the lithium ion battery negative electrode sheet, and the preparation method thereof refers to the preparation method of the lithium ion battery negative electrode sheet and the button half-cell in Example 1, except that the slurry does not contain any phosphorus-sulfur compounds.
[0176] Example 4
[0177] This embodiment 4 provides a lithium ion battery negative electrode sheet and a button half-cell based on the lithium ion battery negative electrode sheet. The preparation method thereof is the same as the preparation method of the lithium ion battery negative electrode sheet and the button half-cell in embodiment 1, with the only difference being that the negative electrode active material is adjusted from commercial graphite material to nano silicon carbon material, and the composite mass percentage of phosphorus-sulfur compounds is adjusted to 2%.
[0178] Comparative Example 2
[0179] Comparative Example 2 provides a lithium ion battery negative electrode sheet and a button half-cell based on the lithium ion battery negative electrode sheet, and the preparation method thereof refers to the preparation method of the lithium ion battery negative electrode sheet and the button half-cell in Example 4, except that the slurry does not contain any phosphorus-sulfur compounds.
[0180] Example 5
[0181] This embodiment 5 provides a battery separator, which includes a polyethylene separator body and a fast ion material. The fast ion material has a three-dimensional network structure and is distributed in the gaps and surface of the polyethylene separator body.
[0182] The preparation method of the battery separator is as follows:
[0183] Li2S and P2S5 were mixed in a tetrahydrofuran solvent at a molar ratio of 3:2, and stirred thoroughly (stirred for 15 min at 500 rpm) to form a second dispersion, wherein the total mass of Li2S and P2S5 was 15% of the total mass of the second dispersion. A polyethylene diaphragm was immersed in the second dispersion as the diaphragm body, and Li2S was slowly added to the second dispersion while maintaining continuous stirring, wherein the amount of Li2S added was such that the ratio of the final molar amount of Li2S to the molar amount of P2S5 was 3:1, and the stirring was continued at a stirring speed of 500 rpm for 60 min, so that the lithiated phosphorus-sulfur compound Li3PS4 was precipitated and attached to the gaps of the polyethylene diaphragm. The wet diaphragm was taken out and placed in a vacuum oven and dried at 60 ° C for 3 h to obtain a battery diaphragm.
[0184] The battery separator was used, the battery pole piece provided in Comparative Example 1 was used as the working electrode, and the lithium sheet was used as the counter electrode to assemble a button-type half-cell.
[0185] Comparative Example 3
[0186] Comparative Example 3 provides a battery separator and a button half-cell based on the battery separator. The battery separator is a currently known polyethylene separator, and the preparation process of the button half-cell is the same as that of Example 5.
[0187] Test Example 1
[0188] In this test example 1, the button half-cells prepared in Example 1 and Comparative Example 1 were disassembled to obtain the negative electrode sheets of the lithium-ion batteries. The electrode material layer of the negative electrode sheets of the lithium-ion batteries was tested by Raman spectroscopy. The test results are shown in Figure 4 .
[0189] Figure 4 In the figure, the horizontal axis Raman shfit is the Raman shift, the vertical axis Intensity is the signal intensity, and the dotted line 1 represents the PS4 of the electrode material layer in Example 1. 3- Characteristic peaks, dotted line 2 represents the characteristic peak of LiO2 in the electrode material layer in Example 1, and dotted line 3 represents the characteristic peak of graphite in the electrode material layer in Example 1. Figure 4 Curve 4 in FIG. 4 represents the graphite characteristic peak of the electrode material layer in Comparative Example 1. It can be seen that PS4 can be observed in the electrode material layer of the negative electrode sheet of the battery provided in Example 1. 3- Characteristic peaks and LiO2 characteristic peaks, there are corresponding chemical bonds in the lithiated phosphorus-sulfur compound, it can be seen that Example 1 effectively synthesized the lithiated phosphorus-sulfur compound.
[0190] The electrode material layer of the negative electrode sheet of the lithium-ion battery was tested by X-ray photoelectron spectroscopy. The test results are shown in Figure 5 and Figure 6 , Figure 5 and Figure 6 In the figure, the horizontal axis Binding energy is the atomic energy, and the vertical axis Intensity is the signal intensity. Figure 5 This is the XPS-P2p spectrum of the electrode material layer of the negative electrode sheet of the lithium ion battery in Example 1, Figure 6 The XPS-S2p spectrum of the electrode material layer of the negative electrode sheet of the lithium-ion battery in Example 1. The line 01 in both figures represents PS4 3- The total characteristic peaks formed by chemical bonds, lines 011 and 012 represent PS4 3- PS4 corresponding to the two energy levels in the case of chemical bond splitting 3- Chemical bond characteristic peaks. Figure 5 and Figure 6 It can be seen that PS4 exists in both P2p and S2p orbitals 3- Chemical bonds, which can explain that there are corresponding phosphorus-sulfur chemical bonds in the lithiated phosphorus-sulfur compounds, which shows that the phosphorus-sulfur compounds are effectively synthesized.
[0191] Figure 7The following are the SEM images and EDS element distribution images of the surface of the electrode material layer of the negative electrode sheet of the lithium ion battery in Example 1. Figure 7 As can be seen from the SEM image, the surface structure of the electrode material layer is relatively loose, so that there are internal gaps to accommodate fast ion materials. Figure 7 EDS-C, EDS-S, and EDS-P in the figure represent the distribution of C, S, and P elements, respectively (the gray-white dots or areas different from the black background in these figures are the corresponding elements). Figure 7 The EDS-C in the graphite anode material characterizes the distribution of the active material, which is the commercial graphite anode material. Figure 7 The SEM images match. Figure 7 The EDS-S and EDS-P in the figure characterize the distribution of fast ion materials. It can be seen that within any selected shooting sampling range (5μm*5μm), the characteristic element signals (P elements and S elements) of densely distributed fast ion materials can be observed, which indicates that the fast ion materials are distributed on the surface of the electrode material layer in a three-dimensional network structure and have spatial distribution continuity.
[0192] Figure 8 The following is a SEM image and EDS element distribution diagram of the cross section of the electrode material layer of the negative electrode sheet of the lithium ion battery in Example 1. Figure 8 From the SEM image, it can be seen that the cross-sectional structure of the electrode material layer is relatively loose, so that there are internal gaps to accommodate the fast ion material. In addition, Figure 8 The thickness of the electrode material layer is shown to be 73 μm. Figure 8 EDS-C, EDS-S, and EDS-P in the figure represent the distribution of C, S, and P elements, respectively (the gray-white dots or areas different from the black background in these figures are the corresponding elements). Figure 8 The EDS-C in the graphite anode material characterizes the distribution of the active material, which is the commercial graphite anode material. Figure 8 The SEM images match. Figure 8 The EDS-S and EDS-P in the figure characterize the distribution of fast ion materials. It can be seen that within any selected shooting sampling range, the characteristic element signals (P elements and S elements) of densely distributed fast ion materials can be observed, which indicates that the fast ion materials are distributed in the cross-section of the electrode material layer in a three-dimensional network structure, and penetrate the electrode material layer along its thickness direction, with spatial distribution continuity.
[0193] Test Example 2
[0194] This test example 2 performs a performance test on the button-type half-cells provided in Examples 1, 2, 3 and Comparative Example 1, wherein: Fig. 9 The first cycle charge and discharge curves of the button-type half-cells provided in Examples 1, 2, 3 and Comparative Example 1 are as follows: Fig. 9The horizontal axis Specificcapacity is the specific capacity, and the vertical axis Voltage is the voltage. Fig. 9 The button-type half-cell of Example 1 is defined as A, the button-type half-cell of Example 2 is defined as B, the button-type half-cell of Example 3 is defined as C, and the button-type half-cell of Comparative Example 1 is defined as D. Fig. 9 It can be calculated that the first coulombic efficiency of the button half-cells provided in Examples 1, 2, 3 and Comparative Example 1 are 92.8%, 84.1%, 76.9% and 66.3%, respectively. It can be seen that the addition of fast ion materials is more beneficial to improving the first coulombic efficiency of the battery.
[0195] Fig.10 The charge and discharge curves of the button-type half-cells provided in Examples 1, 2, 3 and Comparative Example 1 at a current density of 1C are shown in FIG. Fig.10 The horizontal axis Specific capacity is the specific capacity, and the vertical axis Voltage is the voltage. Fig.10 The button-type half-cell of Example 1 is defined as A, the button-type half-cell of Example 2 is defined as B, the button-type half-cell of Example 3 is defined as C, and the button-type half-cell of Comparative Example 1 is defined as D. In the test voltage range of 0 to 0.4 V, the charge and discharge voltage difference of the button-type half-cell provided in Comparative Example 1 is 134 mV, and the charge and discharge voltage difference of the button-type half-cell provided in Example 3 is 94 mV. It can be seen that with the gradual increase of the content of fast ion material in the battery electrode, the polarization effect of the battery is significantly improved.
[0196] In addition, it was also tested that at a current density of 0.2C, the mass specific capacity of the button half-cells provided in Comparative Example 1, Example 1, Example 2, and Example 3 was 357 mAh·g -1 、367mAh·g -1 、370mAh·g -1 and 370mAh·g -1 When the current density rises to 4C and the lithiation time is fixed at 15min, the mass specific capacity of the button half-cells provided in Comparative Example 1, Example 1, Example 2, and Example 3 is 154mAh·g -1 、185mAh·g -1 、191mAh·g -1 1 and 191 mAh g -1 It can be seen that as the content of fast ion materials in the battery pole piece gradually increases, the rate performance of the battery pole piece also gradually improves.
[0197] Test Example 3
[0198] This test example 3 performs a performance test on the button-type half-cells provided in Example 4 and Comparative Example 2, wherein: Fig.11The cycle specific capacity curve of the button half-cell provided for Example 4 and Comparative Example 2, Fig.11 The horizontal axis Cycle number is the number of cycles, and the vertical axis Specificcapacity is the specific capacity. Fig.11 The button-type half-cell of Example 4 is defined as E, and the button-type half-cell of Comparative Example 2 is defined as F. Fig.11 It can be seen that the first charge specific capacity of the button-type half-cell provided in Example 4 is about 1191 mAh / g. When the charge rate is increased, compared with the initial current density charge of 0.2C / discharge of 0.2C, the capacity retention rate of the button-type half-cell provided in Example 4 is about 69.1% under the current density charge of 5.0C / discharge of 0.2C. However, the capacity retention rate of the button-type half-cell provided in Comparative Example 2 under the same test conditions is only 28.6%. It can be seen that the rate performance of the button-type half-cell provided in Example 4 is significantly higher than the rate performance of the button-type half-cell provided in Comparative Example 2.
[0199] Fig.12 The cyclic coulombic efficiency curves of the button half-cells provided in Example 4 and Comparative Example 2 are as follows: Fig.12 The horizontal axis Cycle number is the number of cycles, and the vertical axis Coulombic Efficiency is the Coulombic efficiency. Fig.12 The button-type half-cell of Example 4 is defined as E, and the button-type half-cell of Comparative Example 2 is defined as F. Fig.12 It can be seen that in the 100-cycle long cycle test, the average coulombic efficiency (99.44%) of the button-type half-cell provided in Example 4 is higher than the average coulombic efficiency (98.94%) of the button-type half-cell provided in Comparative Example 2, and the button-type half-cell provided in Example 4 has better electrode reaction kinetics and higher electrode reaction reversibility.
[0200] Test Example 4
[0201] In this test example 4, the specific capacities of the button-type half-cells provided in Examples 1 to 5 and Comparative Examples 1 to 3 at different current densities are listed in Table 1, and the corresponding capacity retention rates are also listed.
[0202] Table 1
[0203]
[0204] It can be seen from Table 1 that by arranging fast ion materials with a three-dimensional network structure in the battery pole pieces and battery separators, the active ion transport kinetics can be significantly improved and the battery rate performance can be enhanced.
[0205] The above description is only for the purpose of facilitating those skilled in the art to understand the technical solution of the present disclosure and is not intended to limit the present disclosure. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present disclosure shall be included in the protection scope of the present disclosure.
Claims
1. A battery pole piece, characterized in that: The battery pole piece includes a current collector and an electrode material layer located on the surface of the current collector; The active material, the conductive agent and the fast ion material are combined with the binder and integrally bonded to the current collector. The fast ion material is distributed in the electrode material layer in a three-dimensional network structure, and the fast ion material is located in the internal gaps and surface of the electrode material layer.
2. The battery electrode according to claim 1, characterized in that: The fast ion material is attached to a surface of at least one of the active material, the conductive agent, and the binder.
3. The battery pole piece according to claim 1, characterized in that: The battery pole piece is used for a lithium-ion battery, and the fast ion material is at least one of a lithiated phosphorus-sulfur compound, a lithiated silicon-sulfur compound, a lithiated germanium-sulfur compound, a lithiated tin-sulfur compound, a lithiated silicon-phosphorus compound, a lithiated germanium-phosphorus compound, a lithiated tin-phosphorus compound, a lithiated silicon-phosphorus-sulfur compound, a lithiated germanium-phosphorus-sulfur compound, and a lithiated tin-phosphorus-sulfur compound; Alternatively, the battery pole piece is used for a sodium ion battery, and the fast ion material is at least one of a sodium-containing phosphorus-sulfur compound, a sodium-containing silicon-sulfur compound, a sodium-containing germanium-sulfur compound, a sodium-containing tin-sulfur compound, a sodium-containing silicon-phosphorus compound, a sodium-containing germanium-phosphorus compound, a sodium-containing tin-phosphorus compound, a sodium-containing silicon-phosphorus-sulfur compound, a sodium-containing germanium-phosphorus-sulfur compound, and a sodium-containing tin-phosphorus-sulfur compound; Alternatively, the battery pole piece is used for a potassium ion battery, and the fast ion material is at least one of a potassium-containing phosphorus-sulfur compound, a potassium-containing silicon-sulfur compound, a potassium-containing germanium-sulfur compound, a potassium-containing tin-sulfur compound, a potassium-containing silicon-phosphorus compound, a potassium-containing germanium-phosphorus compound, a potassium-containing tin-phosphorus compound, a potassium-containing silicon-phosphorus-sulfur compound, a potassium-containing germanium-phosphorus-sulfur compound, and a potassium-containing tin-phosphorus-sulfur compound.
4. The battery pole piece according to any one of claims 1 to 3, characterized in that: The mass of the fast ion material is 0.1%-20% of the total mass of the electrode material layer.
5. A battery separator, characterized in that: The battery separator comprises a separator body and a fast ion material. The fast ion material is distributed in the separator body in a three-dimensional network structure, and the fast ion material is located in the gaps and surface of the separator body.
6. The battery separator according to claim 5, characterized in that: The battery separator is used for lithium-ion batteries, and the fast ion material is at least one of a lithiated phosphorus-sulfur compound, a lithiated silicon-sulfur compound, a lithiated germanium-sulfur compound, a lithiated tin-sulfur compound, a lithiated silicon-phosphorus compound, a lithiated germanium-phosphorus compound, a lithiated tin-phosphorus compound, a lithiated silicon-phosphorus-sulfur compound, a lithiated germanium-phosphorus-sulfur compound, and a lithiated tin-phosphorus-sulfur compound; Alternatively, the battery separator is used for a sodium ion battery, and the fast ion material is at least one of a sodium-containing phosphorus-sulfur compound, a sodium-containing silicon-sulfur compound, a sodium-containing germanium-sulfur compound, a sodium-containing tin-sulfur compound, a sodium-containing silicon-phosphorus compound, a sodium-containing germanium-phosphorus compound, a sodium-containing tin-phosphorus compound, a sodium-containing silicon-phosphorus-sulfur compound, a sodium-containing germanium-phosphorus-sulfur compound, and a sodium-containing tin-phosphorus-sulfur compound; Alternatively, the battery separator is used for a potassium ion battery, and the fast ion material is at least one of a potassium-containing phosphorus-sulfur compound, a potassium-containing silicon-sulfur compound, a potassium-containing germanium-sulfur compound, a potassium-containing tin-sulfur compound, a potassium-containing silicon-phosphorus compound, a potassium-containing germanium-phosphorus compound, a potassium-containing tin-phosphorus compound, a potassium-containing silicon-phosphorus-sulfur compound, a potassium-containing germanium-phosphorus-sulfur compound, and a potassium-containing tin-phosphorus-sulfur compound.
7. The battery separator according to claim 5 or 6, characterized in that: The mass of the fast ion material is 0.1%-20% of the total mass of the battery separator.
8. An electrochemical cell, characterized in that The electrochemical cell comprises at least one of the battery pole piece according to any one of claims 1 to 4 and the battery separator according to any one of claims 5 to 7.
9. The electrochemical cell according to claim 8, characterized in that The electrochemical cells include lithium ion batteries, sodium ion batteries, and potassium ion batteries.
10. A method for preparing a battery electrode, characterized in that: The battery electrode sheet is as described in any one of claims 1 to 4, and the method for preparing the battery electrode sheet comprises: Providing a first dispersion, wherein the first dispersion includes a precursor of a fast ion material, wherein the precursor of the fast ion material is a precursor material capable of forming the fast ion material by lithiation, sodiumization or potassiumization; Dispersing an active material, a conductive agent, and a binder in the first dispersion liquid to obtain a slurry; The slurry is coated on a current collector and dried to obtain a pole piece intermediate; The pole piece intermediate is subjected to lithium, sodium or potassium embedding treatment to obtain the battery pole piece.
11. The method for preparing a battery pole piece according to claim 10, characterized in that: The precursor of the fast ion material is selected from at least one of phosphorus sulfur compounds, silicon sulfur compounds, germanium sulfur compounds, tin sulfur compounds, silicon phosphorus compounds, germanium phosphorus compounds, tin phosphorus compounds, silicon phosphorus sulfur compounds, germanium phosphorus sulfur compounds, and tin phosphorus sulfur compounds.
12. The method for preparing a battery pole piece according to claim 10, characterized in that: The providing of the first dispersion comprises: Mixing and grinding a plurality of single-substance raw materials in sequence to obtain a mixed material, wherein the plurality of single-substance raw materials respectively correspond to a plurality of elements in the precursor of the fast ion material; Sintering the mixed material to obtain a precursor of the fast ion material; The precursor of the fast ion material is dispersed in a first solvent to obtain the first dispersion.
13. The method for preparing a battery pole piece according to claim 12, characterized in that: The operating conditions of the sintering process include at least one of the following conditions: vacuum atmosphere, inert environment, and a sintering temperature of 300° C.-900° C.
14. A method for preparing a battery separator, characterized in that: The battery separator is as described in any one of claims 5 to 7, and the preparation method of the battery separator comprises: Providing a second dispersion, wherein the second dispersion includes a plurality of different raw material compounds, wherein the plurality of different raw material compounds can generate fast ion materials through a chemical reaction; Immersing the diaphragm body in the second dispersion, adding an excessive amount of the raw material compound with the lowest solubility among the multiple different raw material compounds to the second dispersion, so that the multiple different raw material compounds generate the fast ion material through a chemical reaction, and the fast ion material precipitates and adheres to the diaphragm body to obtain a wet diaphragm; The wet separator is dried to obtain the battery separator.
15. The method for preparing a battery separator according to claim 14, characterized in that: The plurality of different raw material compounds include a first raw material compound and a second raw material compound; The first raw material compound includes element A and element B, wherein element A is lithium, sodium or potassium, and element B is one of phosphorus, sulfur, silicon, germanium and tin; The second raw material compound includes element C and element D, wherein element C and element D are each independently selected from one of phosphorus, sulfur, silicon, germanium, and tin.
16. The method for preparing a battery separator according to claim 15, characterized in that: The plurality of different raw material compounds further includes a third raw material compound; The third raw material compound includes element E and element F, wherein element E and element F are each independently selected from one of phosphorus, sulfur, silicon, germanium, and tin.
Citation Information
Cited By
Negative pole piece and preparation method thereof, lithium ion battery and power utilization device
CN120581538A